RELIGIOUS GUIDANCE AND COUNSELING STRATEGIES IN BUILDING THE INDEPENDENCE OF PRAYER SERVICES FOR CHILDREN WITH DISABILITIES AT SLB NEGERI 1 MATARAM - Wahid, Lalu Abdurrachman; Wijayanti, Kartika; Suharti (Universitas Islam Negeri (UIN) Mataram, 2022)
This study aims to determine the strategy or method used to build the independence of prayer for children with disabilities and the inhibiting factors and supporting factors for the implementation of religious guidance and counseling to build the independence of prayer for children with disabilities. The type of research used is descriptive-qualitative, with data collection techniques using observation, interviews, and documentation. The primary data sources in this study were observations and interviews with principals, classroom teachers, and parents of students. Furthermore, secondary data sources in this study were obtained through documentation in the form of photos of student activities and books or literature related to religious guidance strategies and children with disabilities in schools. Data analysis in this study includes data reduction, data display, and verification of data findings, as well as drawing research conclusions. Furthermore, checking the validity of the data through source triangulation and technique triangulation The results showed that the strategy of religious guidance and counseling in building the independence of prayer for children with disabilities that was applied by teachers in schools did not have a special strategy and that in its implementation it followed the abilities of students and was carried out flexibly. In religious guidance and counseling for children with disabilities, the classroom teacher uses the lecture method, the demonstration method, and individual learning methods. Then, the inhibiting factors in building the independence of prayer for children with disabilities are the lack of teachers and the disturbances that students have. While the supporting factors are adequate facilities and infrastructure and support from parents and guardians of students, no less important is the enthusiasm of children to learn.